2010
DOI: 10.1136/bjo.2009.172601
|View full text |Cite
|
Sign up to set email alerts
|

Association among low whole blood viscosity, haematocrit, haemoglobin and diabetic retinopathy in subjects with type 2 diabetes

Abstract: Results demonstrate the association among low viscosity, haemoglobin, haematocrit and diabetic retinopathy. The mechanisms responsible for this association can be hypothesised. Reduced haemoglobin might cause direct organ damage. Low blood viscosity, through the reduction of shear stress, might inhibit the anti-atherogenic functions of endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 25 publications
1
37
0
1
Order By: Relevance
“…Individuals with anemia were more likely to develop DR than individuals without anemia, perhaps because of anemia-induced retinal hypoxia. Hypoxia may alter angiogenesis, capillary permeability, vasomotor response, and cell survival,[27] These results are consistent with those reported in the ETDRS, in which low hematocrit was identified as an independent risk-factor for the development of high-risk PDR and visual impairment. [28] Another large cross-sectional study showed that the odds ratio of having any retinopathy and also risk of severe retinopathy were higher for individuals with an hemoglobin level of < 12 g/dl, as compared with those level ≥ 12 g/dl.…”
Section: Discussionsupporting
confidence: 89%
“…Individuals with anemia were more likely to develop DR than individuals without anemia, perhaps because of anemia-induced retinal hypoxia. Hypoxia may alter angiogenesis, capillary permeability, vasomotor response, and cell survival,[27] These results are consistent with those reported in the ETDRS, in which low hematocrit was identified as an independent risk-factor for the development of high-risk PDR and visual impairment. [28] Another large cross-sectional study showed that the odds ratio of having any retinopathy and also risk of severe retinopathy were higher for individuals with an hemoglobin level of < 12 g/dl, as compared with those level ≥ 12 g/dl.…”
Section: Discussionsupporting
confidence: 89%
“…Important increases in BV have been reported in diabetic retinopathy, and it has been hypothesized that these changes lead to a prolonged reduction in the supply of oxygen and nutrients to the capillaries, causing the development of angiopathy (31,32). Once retinopathy has developed, its progression may be favored by a reduction in BV and hemoglobin (33). Overall, changes in viscosity in diabetic patients are accepted as common and as a result of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic patients with retinopathy show higher blood viscosity than diabetics without retinopathy at both high and low shear rates [37]. However, another study came to the opposite conclusion [39]. Blood viscosity in diabetic patients who have experienced complications, such as microalbuminuria and nephropathy, is also higher than that in patients without such complications [40,41].…”
Section: Abnormalities In Blood Viscosity Associated With Diabetes Mementioning
confidence: 99%